Practice and prospects of indigenous homestead based approaches to prevention of malaria; a case study of a high malaria transmission area in Uganda - Waako, Paul J.; Nsubuga, Rebecca N.; Sebulime, Peregrine; Tabuti, John R.S. (Scientific Research and Essays, 2010)
Environmental sanitation and indigenous practices based on homestead characteristics have not been emphasized in national malaria control strategies. This study explored homestead characteristics, housing attributes, indigenous practices and knowledge of malaria in a rural high malaria transmission community in Uganda. Structured interviews and direct observations of housing attribute and homestead characteristics were carried out in 100 randomly selected homesteads in Kaliro District, Uganda. Plants believed to be mosquito repellants were observed in a number of homesteads and most respondents correctly described malaria symptoms. Almost all homesteads (99%) had large crops grown around them and were close to kraals (within 50 m, 88%). A number of homesteads were in easy reach of un-protected water springs (49%), 32% had material that could harbour mosquitoes (e.g. tins or ditches). The community had good knowledge of malaria and its prevention. Homesteads had modifications aimed at reducing malaria transmission. Despite this knowledge, the environment of most homesteads was conducive for the survival and faster multiplication of malaria vectors and this collaborates with the high prevalence of malaria found in the study area. There is need to develop and pilot interventions focusing on modifications of homestead characteristics and housing attributes for sustainable control of malaria.
Keywords: Malaria; Indigenous; Homestead; Prevention